Low- or moderate-carbohydrate calorie-restricted diets have similar effects on body composition and taekwondo performance after high-carbohydrate recovery meals - Hsu, C.; Huang, Y.-W.; Lin, S.-M.; Lu, C.-S.; Chen, C.-Y.; Chang, C.-K. (European Journal of Sport Science, 2023)
Low-carbohydrate (LC) diets are popular among general and athletic populations attempting to lose body mass. This study investigated the effect of a 7-day LC or moderate-carbohydrate (MC) calorie-restricted diet followed by 18-h recovery on body composition and taekwondo-specific performance. In this randomised cross-over study, 12 male taekwondo athletes consumed an LC (10% of carbohydrate, 41% of protein, 49% of fat, and 15.8 ± 0.4 kcal/kg/day) or an isocaloric MC diet (60% of carbohydrate, 30% of protein, and 10% of fat) for 7 days. The participants then consumed a carbohydrate-rich recovery dinner (39.2 ± 3.1 kcal/kg) followed by breakfast (6.2 ± 0.4 kcal/kg) in both the trials. Three repeated sprint ability (RSA) tests were conducted after breakfast. The taekwondo-specific reaction battery was administered before the first RSA test and after each RSA test. The participants experienced similar magnitudes of significant loss of body mass in the LC (-2.4 ± 1.7%) and MC (-2.3 ± 1.7%) trials. Fat mass and fat percentage significantly decreased in the MC trial but remained unchanged in the LC trial after body mass loss. Fat free mass was maintained in both the trials. The average and peak power in the RSA tests and the premotor reaction time were similar between the trials. The participants experienced significantly higher fatigue in the LC trial. In conclusion, both the diets can help athletes rapidly lose body mass while maintaining performance as long as an adequate amount of carbohydrate is consumed during the recovery period.